Design of an embedded inverse-feedforward biomolecular tracking controller for enzymatic reaction processes. (6th April 2017) - Foo, Mathias; Kim, Jongrae; Sawlekar, Rucha; Bates, Declan G.
Abstract : Graphical abstract: Abstract : Highlights: A new approach for the design of embedded biomolecular controllers is presented. The approach circumvents fundamental problems in chemical reaction network theory. The control architecture combines inverse-feedforward and feedback control. The controller requires fewer chemical reactions for experimental implementation. Abstract: Feedback control is widely used in chemical engineering to improve the performance and robustness of chemical processes. Feedback controllers require a 'subtractor' that is able to compute the error between the process output and the reference signal. In the case of embedded biomolecular control circuits, subtractors designed using standard chemical reaction network theory can only realise one-sided subtraction, rendering standard controller design approaches inadequate. Here, we show how a biomolecular controller that allows tracking of required changes in the outputs of enzymatic reaction processes can be designed and implemented within the framework of chemical reaction network theory. The controller architecture employs an inversion-based feedforward controller that compensates for the limitations of the one-sided subtractor that generates the error signals for a feedback controller. The proposed approach requires significantly fewer chemical reactions to implement than alternative designs, and should have wide applicability throughout the fields of synthetic biology and biological engineering.